Conservação do macaco-prego-galego em Alagoas : ocupação, defaunação e manejo em uma paisagem brasileira fragmentada - Lins, Poliana Gabriele Alves de Souza (2022)
The state of Alagoas has confirmed the occurrence of the Threatened medium-sized monkey, Sapajus flavius, the blond capuchin monkey. Its conservation levels are a consequence of lost habitat, hunting, and illegal trade. Meanwhile, wildlife care centers are getting overwhelmed because of primate trafficking. This project aims to evaluate the quality of the landscape with and without the blond capuchin monkeys to model their occupation. When performing these samplings, our objectives are: (1) to infer the effect of the landscape on the distribution of species in the state of Alagoas; (2) to obtain defaunation rates to establish the risk for conservation in each fragment visited; (3) combine suitability and risk to classify the remnants and define a management plan for their conservation in the State. We conduct monthly excursions to obtain data on the detection of the blond capuchin monkeys, a list of mammals weighing more than 500g inhabiting the fragments, and information on the hunting, logging, and protection status of the fragments. I also obtained physical and biological variables of the fragment, whether inhabited or not by primates. We found that there are more blond capuchin monkeys in fragments of Caatinga than of Atlantic Forest, but only 20% of them were occupied, and that the chances of occupying fragments increase with the bigger area and more protection. 57% of the fragments studied have more than74.9% mammalian defaunation, that is, less than 4 genera of mammals weighing more than 500g. By subtracting the chances of finding the monkeys by the defaunation suffered we found two fragments of Atlantic Forest that should be a priority of conservation because they are considered the best refuges of the target species. The species is under great risk in the other fragments where it is found, given the levels of defaunation reached. A scenario in which society engages and invests in environmental actions should consider reintroducing animals in defaunated fragments that still have an intermediate level of suitability. However, a political scenario where society does not want to invest in the environment needs to prioritize education to realize the connection of ecosystem services that may be lost and create the expectation of providing this for their children.